Supporting children when parents separate : embedding a crisis intervention approach within family justice, education and mental health policy / Mervyn Murch. - Murch, Mervyn (Policy Press, 2018)
A fresh approach to supporting children who experience parental separation and divorce. Murch argues for preventative intervention which responds to children's worries when they first present them, without waiting until things have gone badly wrong.